Expanding the scope of mast cell disease: Does mast cell‐derived TNF play a role in immune‐mediated chronic illness and autoimmunity? - Rachel da Silveira Gorman; Iffath Unissa Syed (Rheumatology & Autoimmunity)
Abstract Increasing evidence underscores the vital significance of diverse mast cell mediators in inflammatory illness, yet diagnostic criteria for mast cell activation syndrome still focus predominantly on a solitary mediator, tryptase. Therapeutic interventions, conversely, tend to prioritize histamine, prostaglandins, and leukotrienes. This article, via a review of both experimental and clinical findings, spotlights the mechanisms of action of an important mast cell mediator – tumor necrosis factor (TNF), and elucidates the intricate linkages between mast cell dysfunction, chronic illness, and autoimmunity. After providing an overview of the role of mast cell‐derived TNF in inflammatory illnesses and viral infections, we hypothesize the interplay between mast cell‐derived TNF and mitochondrial dysfunction, microglial activation, and the hypothalamic‐pituitary‐adrenal axis and the pathways of action on mast cells of treatments such as high‐dose melatonin and low‐dose naltrexone.